SIMBOL DAN IRONI DALAM CERPEN THE LOTTERY, KARYA SHIRLEY JACKSON - Syam, Essy (Universitas Lancang Kuning, 2012)
A work, particularly literary work consists of many interesting elements to analyze. It's true for I have .figured out that